Variability in Uremic Control during Continuous Venovenous Hemodiafiltration in Trauma Patients - Sigrid Beitland; Kjetil Sunde; Harald Moen; Ingrid Os (Critical Care Research and Practice)
Introduction. Acute kidney injury (AKI) necessitating continuous renal replacement therapy (CRRT) is a severe complication in trauma patients (TP). We wanted to assess daily duration of CRRT and its impact on uremic control in TP. Material and Methods. We retrospectively reviewed adult TP, with or without rhabdomyolysis, with AKI undergoing CRRT. Data on daily CRRT duration and causes for temporary stops were collected from the first five CRRT days. Uremic control was assessed by daily changes in serum urea (Δurea) and creatinine (Δcreatinine) concentrations. Results. Thirty-six TP were included with a total of 150 CRRT days, 17 (43%) with rhabdomyolysis. The median (interquartile range (IQR)) time per day with CRRT was 19 (15–21) hours. There was a significant correlation between daily CRRT duration and Δurea (r=0.60, P≤0.001) and Δcreatinine (r=0.43; P=0.012). CRRT pauses were caused by filter clotting (54%), therapeutic interventions (25%), catheter related problems (10%), filter timeout (6%), and diagnostic procedures (6%). Rhabdomyolysis did not affect the CRRT data. Conclusions. TP undergoing CRRT had short daily CRRT duration causing reduced uremic control. Clinicians should modify their daily clinical practice to improve technical skills and achieve sufficient dialysis dose.